Kirk-Othmer Encyclopedia of Chemical Technology 2003
DOI: 10.1002/0471238961.1415021218150209.a01.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst Deactivation and Regeneration

Abstract: This article focuses on the causes, mechanisms, prevention, modeling, and treatment (experimental and theoretical) of deactivation. The causes of deactivation are basically of three kinds: chemical, mechanical, and thermal. The five intrinsic mechanisms of catalyst decay, ( 1 ) poisoning, ( 2 ) fouling, ( 3 ) thermal degradation, ( 4 ) chemical degradation, and ( 5 ) mechanical failure, vary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
36
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 187 publications
(179 reference statements)
3
36
0
2
Order By: Relevance
“…Excellent reviews are reported elsewhere. 24,25 Following Bartolomew, there are basically five 50 types of mechanisms of catalyst deactivation in gas-phase that are compiled in Table 1. These five types can be grouped, based on the nature of the mechanism, as physical, thermal and chemical.…”
Section: Overview Of Mechanisms Of Catalyst Deactivationmentioning
confidence: 99%
See 2 more Smart Citations
“…Excellent reviews are reported elsewhere. 24,25 Following Bartolomew, there are basically five 50 types of mechanisms of catalyst deactivation in gas-phase that are compiled in Table 1. These five types can be grouped, based on the nature of the mechanism, as physical, thermal and chemical.…”
Section: Overview Of Mechanisms Of Catalyst Deactivationmentioning
confidence: 99%
“…Numerous reviews, proceedings and investigations address the mechanisms of catalyst deactivation when gas reactants are used and the possibilities of regeneration or 65 prevention of the deactivation. 24,25 . However, much less attention 70 has been paid to understand the deactivation processes in liquid media, probably due to the fact that most of the industrial catalytic processes are carried out in gas phase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Os catalisadores podem perder a sua atividade catalítica, como resultado de uma série de produtos químicos indesejáveis presentes originalmente nos combustíveis e por mudanças físicas [12][13][14][15][16][17]. Os tipos de fenôme-nos da inativação podem ser divididos em três categorias: química, térmica e envelhecimento mecânico [14,15].…”
Section: Introductionunclassified
“…Os tipos de fenôme-nos da inativação podem ser divididos em três categorias: química, térmica e envelhecimento mecânico [14,15]. A inativação ocorre ao longo da vida útil do catalisador, devido a uma ou à combinação de vários fenô-menos.…”
Section: Introductionunclassified